Stereoselective Synthesis of Dispirooxindoles Incorporating Pyrrolo[2,1-a]isoquinoline via [3+2] Cycloaddition of Azomethine Ylides with a Thiazolo[3,2-a]indole Dipolarophile - Thomas, Noble V.; Meenakshy, C. B.; Leena, Sruthi S.; Deepthi, Ani (Synthesis, 2022)
Highly regio- and stereoselective synthesis of dispiropyrrolo[2,1-a]isoquinoline-oxindoles have been developed by the one-pot three component reaction of isatins, 1,2,3,4-tetrahydroisoquinoline (THIQ), and a thiazolo[3,2-a]indole derivative. The reaction proceeds regioselectively through an exo-Re face approach of the in situ generated tetrahydroisoquinolium ylides towards the dipolarophile yielding the corresponding [3+2] cycloadducts in excellent yields and stereoselectivity.
Keywords: [3+2] cycloaddition; azomethine ylide; 1,2,3,4-tetrahydroisoquinoline; thiazolo[3,2-a]indole; spiropyrrolo[2,1-a]isoquinoline